Insights and comparison of structure–bulk property relationships in low generation hydroxylated polyester dendrimer and hyperbranched polymer prepared from bis-MPA monomer. (28th September 2021) - Chen, Beibei; Syed, Maliha N.; Daymon, Samantha P.; Olson, Brian G.; Kareem, Oluwapelumi O.; Giesen, Joseph A.; Fahs, Gregory B.; Moore, Robert R.; Grayson, Scott M.; Nazarenko, Sergei
Abstract: In this study a second generation, perfectly branched dendrimer (D2) was synthesized using an iterative method via anhydride coupling from a bis-MPA monomer and a pentaerythritol core. The multigram scale production of this dendrimer in the lab enabled a multifaceted investigation of structure-bulk property relationships and a subsequent comparison with those of the second generation of a chemically similar but hyperbranched polymer (HBP2) produced via rapid one-pot synthesis from a bis-MPA monomer and an ethoxylated pentaerythritol core. Several characterization tools such as 1 H NMR, FTIR, DSC, WAXS, and high-pressure dilatometry were employed to explicate fundamental differences and similarities between these two important dendritic polymer subclasses. Specifically, high pressure dilatometry permitted an investigation of temperature and pressure effects on specific volume (PVT) of the dendrimer and its HBP analogue. Fitting PVT data to the Simha-Somcynsky (S–S) equation of state (EOS) for the melt state enabled demonstration the power of this EOS, originally developed for linear polymers, to also fully describe the PVT surfaces of the dendrimer and HBP in this study. Generated molecular parameters from the S–S model were compared with those for other polymeric systems. Finally, fractional free volume for the dendrimer and HBP, determined from the PVT data and the S–S model, at various temperatures and pressures was compared. Graphical abstract: Image 1 Highlights: Bulk properties of a hydroxylated dendrimer and hyperbranched polymer were compared. The HBP contains mesophase formed by aggregates of H-bonded linear chain segments. Determined and compared fractional free volume for the dendrimer and HBP analogue. The fractional free volume of both polymers superimposed when plotted against T-Tg . Showed the Simha-Somcynsky equation of state is applicable to dendritic polymers.